SENSITIZATION OF TiO2 FILMS BY INDONESIAN NATURAL â??BATIKâ? DYES FOR DYE SENSITIZED SOLAR CELLS (DSSC) - , Indriana Kartini, Septina Is Heriyanti, Yateman Arryanto, Chotim ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Sensitization of TiO2 films by Indonesian natural &ldquo